Increased HIV‐1 infection in PBMCs treated in vitro with menstrual cycle phase hormones or medroxyprogesterone acetate likely occurs via different mechanisms. (2nd November 2022) - Bick, Alexis J.; Avenant, Chanel; Tomasicchio, Michele; van der Spuy, Zephne; Hapgood, Janet P.
Abstract: Problem: Both luteal phase progesterone (P4) levels and use of the intramuscular (IM) injectable progestin‐only contraceptive depo‐medroxyprogesterone acetate (DMPA‐IM) have been linked to increased S/HIV acquisition in animal, clinical and in vitro models. Several plausible mechanisms could explain MPA‐induced HIV‐1 acquisition while those for the luteal phase are underexplored. Method of study: Peripheral blood mononuclear cells (PBMCs) were treated with P4 and estrogen at concentrations mimicking the luteal phase, follicular phase or with levels of MPA mimicking peak serum levels in DMPA‐IM users. Cells were infected with an R5‐tropic infectious molecular clone and HIV‐1 infection was measured. A role for the glucocorticoid receptor (GR) was investigated using the GR/PR antagonist RU486. CCR5 protein levels and activation status, assessed by levels of the activation marker CD69, were measured by flow cytometry after treatment in vitro and in PBMCs from naturally‐cycling women or DMPA‐IM users. Results: Both MPA and luteal phase hormones significantly increased HIV‐1 infection in vitro. However, MPA but not luteal phase hormones increased the CD4+/CD8+ T cell ratio, CCR5 protein expression on CD4+ T cells and increased expression of the activation marker CD69. The GR is involved in MPA‐induced, but not luteal phase hormone‐induced increased HIV‐1 infection. In DMPA‐IM users, the frequency of CCR5‐expressing CD3+ and CD8+ cells was higher than for women in the luteal phase. Conclusions: MPA increases HIV‐1 infection in a manner different from that of luteal phase hormones, most likely involving the GR and at least in part changes in the frequency and/or expression of CCR5 and CD69.